Genus Coltivirus (family Reoviridae): genomic and morphologic characterization of Old World and New World viruses - Attoui, H. (Arch Virol, 2002)
We report a genomic and morphologic study of the European Eyach (EYA) virus (genus Coltivirus, family Reoviridae) and a comparative analysis with the American Colorado tick fever (CTF) virus (the type species of the genus). The previously established, but distant, antigenic relationship between these viruses was strengthened by genetic findings (presence of cognate genes, amino acid identity between 55 and 88%, similar conserved terminal motifs, suspected read-through phenomenon in segment 9 of both viruses) and by indistinguishable ultramicroscopic morphologies. Moreover, putative constitutive modifying enzyme activities were suspected to be carried out by homologous viral proteins (RNA-dependent RNA polymerase, methyl/guanylyl transferase, NTPase). These findings, together with the comparative analysis to genomes of south-east Asian isolates, support the recent classification of arboviruses with 12 segments of dsRNA within two distinct genera (genus Coltivirus and genus Seadornavirus) and raise interesting questions about the evolutionary origins of coltiviruses. The previously proposed hypothesis that EYA virus was derived from an ancestral virus introduced in Europe with the migration of lagomorphs from North-America, would imply a divergence date between American and European isolates of over 50 million years ago (MYA). This analysis allows for the first time to propose an evolutionary rate for virus dsRNA genomes which was found to be in the order of 10(−8) to 10(−9) mutations/nt/year, a rate similar to that of dsDNA genomes.